Redescriptions of Scirtidae (Coleoptera: Scirtoidea) described by Carl Henrik Boheman (1796–1868) with notes on Scirtes adustus iversenotatus Pic, 1930 - Ruta, Rafał; Libonatti, María Laura (Zootaxa, 2016)
Boheman described four species of Scirtidae: one from Sweden (Cyphon pallidulus Boheman, 1850), two from South Africa (Elodes caffer Boheman, 1851 & Elodes marginipennis Boheman, 1851), and one from Argentina (Scirtes adustus Boheman, 1858). Cyphon pallidulus Boheman is a junior synonym of Contacyphon ochraceus (Stephens, 1830). Types of the remaining species were never re-examined, and none of them were redescribed. In the present paper, three species are redescribed on the basis of type specimens deposited in the Swedish Natural History Museum in Stockholm. Genitalia are illustrated for the first time and a new combination is proposed: Brachycyphon marginipennis (Boheman, 1851). The type specimen of a variety described by Pic, S. adustus var. diversenotatus, was examined and revealed to represent a distinct species, which is redescribed under the name of Scirtes diversenotatus Pic, 1930 stat. nov. in the present paper.